The third gamma subunit of the gamma-aminobutyric acid type A receptor family. - Herb, A (1992)
Cloned cDNAs encoding a member of the gamma-aminobutyric acid type A receptor gamma-subunit class were isolated from rat-brain-mRNA-derived libraries. The gamma 3 mRNA is present in cortex, claustrum, caudate putamen, and some thalamic nuclei, particularly the medial geniculate nucleus, where it is the predominant gamma-subunit transcript. The gamma 3 gene is expressed at very low levels in cerebellum and hippocampus. In coexpression experiments with the alpha 1 and beta 2 subunits, gamma 3 imparts benzodiazepine binding to gamma-aminobutyric acid type A receptors and forms gamma-aminobutyric acid-gated benzodiazepine-modulated chloride channels that exhibit a larger conductance than alpha 1 beta 2 receptor channels. Furthermore, the presence of gamma 3 in place of gamma 2 in alpha 1 beta 2 gamma x receptors generates a marked decrease in the affinity of agonists while leaving the affinity of antagonists or negative modulators largely unaffected.